The dramatic poetic form in the book of Al-Diyarat by Al-Sabhani - Abdullah, Dalal Maan; Hadi, Salah Kadhim (Al-Adab Journal, 2023)
The beginnings of drama were related to human life, which made it a literary genre inherent to its production in successive ages; And that as a contact with human issues, by re-imagining reality in a literary way that affects the recipient, and by involving many personalities to complete the dramatic work. Therefore, drama was considered one of the most influential arts compared to other arts. Because language is the basis for expression, and this is something that is not found in the rest of the arts, as it contains contemplation and intellectual and emotional disclosure that we do not see in others, as it involves under the style of narration, whether it is poetic or prose narration. His way the theatrical expression takes place at its first appearance, and thereafter the dramatic poetic expression, which is related to thought and social customs among individuals, praising the beautiful behavior, and criticizing the defects of the individual in society, as he combines between highlighting the poet's soul and presenting the story of the audience, at the same time he does not forget to link The reader’s imagination with the feeling of the poet and the community, so that a group of dramatic voices and situations appear to the reader through both types of dialogue and the psychological conflict that dominated the poet at one time, by framing it in a poetic and emotional and dramatic image and presenting it to the reader; To feel the places of its beauty, with the aim of being affected by it and keeping it stuck in his mind.